Putting Giddens into Action: Social Systems and Managerial Agency - Whittington, R (1992)
This article examines the influence of Anthony Giddens on recent work in management studies, especially the contribution of his structurationist pers- pective to understanding managerial agency. A citation analysis and discussion of prominent exponents such as Ranson et al. (1980), Andrew Pettigrew and Hugh Willmott, concludes that Giddens' influence is substantial but lopsided. Giddens' concern for the intersection and tension between different social systems has been particularly neglected. Drawing on the insights of current 'institutionalist' studies of societal influences on organizations, the article builds a structurationist account of managerial agency that is founded on the contradictions within and between different social systems. The article ends by considering the implications of this structurationist account for current concerns with managerial leadership, organizational symbolism and strategic choice.